ØªÙƒÙ†ÙˆÙ„ÙˆØ¬ÙŠØ§ ÙˆØ¥Ù†ØªØ§Ø¬ Ø§Ù„ÙˆØ³Ø§Ø¦Ù„ Ø§Ù„ØªØ¹Ù„ÙŠÙ…ÙŠØ© ÙÙŠ ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© ÙˆØÙ„ÙˆÙ„ Ø§Ù„Ù…Ø´ÙƒÙ„Ø§Øª ÙÙŠÙ‡ - Nugrawiyati, Jepri; Nurwendah, Yusti Dwi (Jurusan Pendidikan Bahasa Arab IAIN Ponorogo, 2019)
Arabic learning has never been separated from many problems that arise in it, both from external factors and internal factors. This makes learning Arabic known as difficult subject and it requires the solving with right solution. On the other hand, technological developments today provide various interesting and amazing offers in the world of education. The rapid development of technology cannot be denied to have a huge impact on education. Learning media which are products of technology become things that cannot be avoided from the world of education including learning Arabic. Therefore, technology and learning media are considered as one of the solutions of problems in learning Arabic language today. Therefore, as technology grows rapidly, media products of Arabic learning can also be produced and developed well by observers or instructors of Arabic language subject so that they should support for better Arabic learning and teaching.With these various facilities, Arabic instructors can use technology and learning media as a means to facilitate learners of Arabic to learn it, which of course must be based on harmony between goals and expected results